SMART Instagram Optimization: A Framework for Building Malabar’s Stronger Brand Awareness and Identity in the Digital Era - Hasbiah, Sitti (PT. Maju Malaqbi Makkarana, 2025)
This study aims to improve the internal capacity of Malabar MSMEs in managing digital marketing through an internal training program designed based on the SMART Framework approach. The main problem faced by Malabar is the lack of staff understanding in managing social media, especially Instagram, which impacts weak brand awareness and brand identity. This study uses a descriptive qualitative approach with a project-based learning method, in which researchers are actively involved in the planning, implementation, and evaluation of the training program. Data were collected through participant observation, semi-structured interviews, and documentation during the training process. The training objectives were formulated specifically, measurable, achievable, relevant, and time-limited, in accordance with the SMART principles. The results showed a significant increase in staff understanding of content planning, creating visual materials consistent with brand identity, and using Instagram analytics features. The post-test showed an increase in the average score of participants, and the MSMEs' digital activities became more structured. These findings indicate that internal training designed with the SMART approach is effective in building staff digital competencies and supporting brand image strengthening on social media. Overall, this study shows that improving internal digital literacy is a strategic step that can strengthen the competitiveness of MSMEs in the ever-evolving digital ecosystem